2014
DOI: 10.3892/mmr.2014.2453
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells improve intestinal integrity during severe acute pancreatitis

Abstract: Severe acute pancreatitis (SAP) is an acute inflammatory disease of the pancreas that involves various distant tissues and organs. This study aimed to investigate post-tissue injury repair by mesenchymal stem cells (MSCs) in a rat model of SAP. A total of 54 pathogen-free adult male SD rats were randomly assigned to the groups SAP, SAP + MSCs and sham-operated (SO). SAP was induced by 4% sodium taurocholate, and MSCs were injected via the dorsal penile vein 1 h later. The amylase activity, and tumor necrosis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The current treatment methods are mostly combinations of internal medicine and surgery [ 2 ]. Biotherapy, which is gradually being accepted by patients, is based on stem cells as a novel therapeutic method that is expected to cure SAP completely [ 4 , 6 , 15 17 , 29 31 ]. MSCs, which are important members of the family of stem cells, are characterized by specific properties such as self-renewal, multilineage differentiation, immunosuppressive effects, and paracrine effects and are also used as vectors for exogenous genes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current treatment methods are mostly combinations of internal medicine and surgery [ 2 ]. Biotherapy, which is gradually being accepted by patients, is based on stem cells as a novel therapeutic method that is expected to cure SAP completely [ 4 , 6 , 15 17 , 29 31 ]. MSCs, which are important members of the family of stem cells, are characterized by specific properties such as self-renewal, multilineage differentiation, immunosuppressive effects, and paracrine effects and are also used as vectors for exogenous genes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since acute pancreatitis is a self-limited condition and pancreatic tissue damage occurs only following severe acute pancreatitis, all included studies investigated the effect of MSC therapy in severe acute pancreatitis. Multiple methods of inducing severe acute pancreatitis were used: injection of Na-taurocholate (7 studies) [ 44 , 46 , 47 , 49 , 50 , 52 ], intraperitoneal injections of caerulein (2 studies) [ 29 , 30 ], L-arginine-induced acute pancreatitis (one study) [ 33 ], and deoxy-STC injection under the pancreatic capsule (1 study) [ 51 ]. All 16 studies showed a reduction in pancreatic tissue damage, necrosis, inflammation, and oedema compared to those of the untreated groups.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven of the 16 studies used BM-MSCs as therapy for severe acute pancreatitis [ 44 52 ]. Except for two studies [ 51 , 52 ], well-characterized MSCs were infused into animals using defined surface markers and mesodermal differentiation according to the criteria of the International Society for Cell Therapy. Nine of the 11 studies further evaluated the mechanism of action of BM-MSCs following severe acute pancreatitis [ 44 49 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…First, the vectors of pri-miR-9-PCDH, PLKO.1-TuD or PCDH ( 8   µg/plate ), pCMVΔ R8.74 expressing HIV gag/pol, Rev and tat ( 5.3   µg/plate ), and pMD2.G expressing VSV-G ( 2.65   µg/plate ) were co-transfected into HEK293T cells by Lipo2000 as previously described 62 . Second, the supernatants were collected at 24 and 48 hr respectively and concentrated by PEG-it Virus Precipitation Solution ( System Biosciences, CA, USA ) or supercentrifugation ( 75,000   ×   g, 2 hr ).…”
Section: Methodsmentioning
confidence: 99%